Determinants of cancer incidence and mortality among people with vitamin D deficiency: an epidemiology study using a real-world population database - Lai, Yi-Chen; Chen, Yu-Han; Liang, Fu-Wen; Wu, Yu-Cih; Wang, Jhi-Joung; Lim, Sher-Wei; Ho, Chung-Han (Frontiers in Nutrition, 2023)
Introduction This study aimed to investigate the determinants of cancer incidence and mortality in patients with vitamin D deficiency using a real-world population database. Methods We utilized the International Diagnostic Classification Code (ICD9:268 / ICD10: E55) to define patients with vitamin D deficiency. Additionally, the Cox regression model was used to estimate overall mortality and identify potential factors contributing to mortality in cancer patients. Results In 5242 patients with vitamin D deficiency, the development of new-onset cancer was 229 (4.37%) patients. Colon cancer was the most prevalent cancer type. After considering confounding factors, patients aged 50–65 and more than 65 indicated a 3.10-fold (95% C.I.: 2.12–4.51) and 4.55-fold (95% C.I.: 3.03–6.82) cancer incidence, respectively compared with those aged <50. Moreover, patients with comorbidities of diabetes mellitus (DM) (HR: 1.56; 95% C.I.: 1.01–2.41) and liver disease (HR: 1.62; 95% C.I.: 1.03–2.54) presented a higher cancer incidence rate than those without DM/ liver disease. In addition, vitamin D deficiency patients with cancer and dementia histories indicated a significantly higher mortality risk (HR: 4.04; 95% C.I.: 1.05– 15.56) than those without dementia. Conclusion In conclusion, our study revealed that vitamin D deficiency patients with liver disease had an increased incidence of cancer, while those with dementia had an increased mortality rate among cancer patients.